APLIKASI PENGINDERAAN JAUH UNTUK ANALISIS PERUBAHAN TUTUPAN LAHAN MANGROVE DI SUNGAI JANGKANG KABUPATEN BENGKALIS,PROVINSI RIAU - , TENGKU AFNILITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Remote sensing has gave many kind of advantages such as for forest monitoring and to mapping the land cover changes. The satellite data such as Alos and Rapid Eye can be used to detect of mangrove forest condition. This research use two different of data types and two different of spatial resolution. The location of this research is on Jangkang River at Bengkalis regency , Riau province. The aims of this research are 1) to map land cover changes in mangrove. 2) to know the accuracy each image satellite data for mangrove mapping and to find out the cause of mangrove land cover changes. This research using Maximum Likelihood classification to detect mangrove cover at Jangkang river. The result of the classification are mangrove, water, thickets, plantations, shrubs, settlements and open land. Accuracy for this research was done by error matrix method to assess the classification result. The results showed that accuracy of land cover for Alos imagery was 98.0% and for Rapid Eye imagery was 89.9%. Based on classification showed that mangrove cover for Alos (2009) imagery has 701.35 ha and for Rapid Eye (2011) imagery has 470 ha. During 2009 â 2011 showed that mangrove at Jangkang river decreased of 231.35 ha in a 2-yrs period.